Integration of Green Marketing and Digital Strategy on the Competitiveness of Cassava-Based SMEs in Sumenep Regency - Raden Khaeru Ahmadi; Siti Saadah; Eny Fitriyah; Evi Susmiati (Universitas KH. Abdul Chalim Mojokerto, 2026)
Micro, Small, and Medium Enterprises (MSMEs) based on local products play a strategic role in regional economic development; however, they continue to face competitiveness challenges, particularly in rural areas. Increasing consumer awareness of environmental issues and the acceleration of digital transformation require MSMEs to adopt sustainable and adaptive marketing strategies. This study aims to examine the effect of green marketing and digital marketing strategies on the sustainable competitiveness of cassava-processing MSMEs in Banasarep Village, Sumenep Regency, and to develop a Smart Eco-MSME model as an integrative approach. This study employs a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were collected through a structured questionnaire with a five-point Likert scale administered to 30 cassava-processing MSMEs selected using purposive sampling. Data analysis involved outer model evaluation, inner model assessment, and hypothesis testing through bootstrapping procedures. The results indicate that green marketing has a positive and significant effect on the sustainable competitiveness of MSMEs. Digital marketing strategies also show a positive and significant effect, with a stronger influence than green marketing. Simultaneously, green marketing and digital marketing explain 67.2% of the variance in sustainable competitiveness. These findings suggest that integrating environmental values with digital technology utilization can create long-term competitive advantages for MSMEs. This study concludes that the Smart Eco-MSME model is effectively applicable to cassava-processing MSMEs in rural areas. Policy implications highlight the importance of local government support in enhancing digital literacy, promoting green marketing practices, and developing a sustainable MSME ecosystem based on local resources.